2007
DOI: 10.1016/j.jcrs.2007.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of accommodation on the anterior and posterior cornea

Abstract: Small cyclotorsional eye movements occurred with accommodation. When these eye movements were accounted for in data analysis, no consistent significant change in the topography of the cornea was found with accommodation across an 8.0 to 9.0 mm corneal diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 39 publications
4
49
0
1
Order By: Relevance
“…Finally, and in spite of these contradictory results among all previous studies [6][7][8][9][17][18][19], it should be taken into account that only three studies assessed corneal changes at different accommodation ranges [6,9,17]. Concretely, these studies reported that corneal changes are not statistically significant during accommodation, and are in agreement with those obtained previously.…”
Section: Central Corneal Thicknesssupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, and in spite of these contradictory results among all previous studies [6][7][8][9][17][18][19], it should be taken into account that only three studies assessed corneal changes at different accommodation ranges [6,9,17]. Concretely, these studies reported that corneal changes are not statistically significant during accommodation, and are in agreement with those obtained previously.…”
Section: Central Corneal Thicknesssupporting
confidence: 83%
“…In this regard, some studies have assessed the corneal periphery (R>7.0 mm), and reported changes in the corneal curvature, volume and aberrations with accommodation [6][7][8]16]. Contrarily, other studies hypothesized that corneal changes with the accommodation are associated with the cyclotorsion produced in the corneal topography [17,18]. Nevertheless, when that rotation was corrected, corneal changes were reduced considerably and were not significant.…”
Section: Central Corneal Thicknessmentioning
confidence: 99%
“…A number of studies (Table 1) have assessed the changes in central ACD during accommodation. Our results are in agreement with those found previously in emmetropic volunteers (4,15,17,18,22,23,25,26) . Bolz et al (4) , who used partial coherence interferometry, found a relative ACD decrease of 4.92% after -4.00 D of vergence.…”
Section: Anterior Chamber Depthsupporting
confidence: 93%
“…Malyugin et al (17) , Read et al (23) , and Tsorbatzoglou et al (25) studied changes in ACD after -3.00 D of accommodation and found that the relative changes were 3.80%, 3.20% and 2.23%, respectively. Finally, Ni et al (18) and Read et al (22) also studied the changes in ACD with accommodation in young eyes with the help of Pentacam HR. After -5 D accommodation, the mean ACD decreased approximately by 0.11 mm and 0.14 mm, respectively.…”
Section: Anterior Chamber Depthmentioning
confidence: 99%
“…21 In our study, HOA RMS and spherical aberration increased with age. Previous studies 11,28 have evaluated the possible role of corneal pseudoaccommodation. With respect to ocular cyclotorsion, examinations did not confirm changes in the topography of the cornea during accommodation, 11,29 nor did our study verify such corneal deviations during accommodation.…”
Section: Discussionmentioning
confidence: 99%